Digitalization and entrepreneurial firms' resilience to pandemic crises: Evidence from COVID-19 and the German Mittelstand - Bürgel, Tobias R.; Hiebl, Martin R.W.; Pielsticker, David I. (Technological forecasting & social change, 2023)
While stressing the relevance of context, the organizational resilience literature has so far not extensively examined resilience in times of healthcare crises such as the ongoing COVID-19 pandemic. The Parasite Stress Theory of Values suggests that such pandemic crises have detrimental impacts on entrepreneurial activity due to social distancing and its effects on interaction, collaboration, and innovation. However, alternatives to personal contact now available thanks to digitalization, have not yet been examined. We expect entrepreneurial firms with more digitalized business models to show higher resilience to pandemic crises, especially those highly affected by globalization and more for non-family businesses than for family businesses. Based on a survey of German Mittelstand firms in the midst of the crisis induced by COVID-19, our findings broadly support our expectations and thus help qualify the Parasite Stress Theory of Values and contribute to a better understanding of organizational resilience in times of pandemic crises. •The Parasite Stress Theory of Values states that pandemic crises reduce entrepreneurial activity due to social distancing.•Nowadays, however, there are alternatives to face-to-face contact thanks to digitalization.•We investigate whether companies with more digitalized business models exhibit higher resilience to pandemic crises.•We find that non-family firms and firms heavily affected by globalization exhibit higher levels of resilience to a pandemic if they had more digitalized business models before the crisis.•Our results help to qualify and extend the Parasite Stress Theory of Values to applications at the organizational level.